2016
DOI: 10.4103/2153-3539.181769
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the use of whole slide imaging for the diagnosis of central nervous system tumors: A pilot study in surgical neuropathology

Abstract: Background:Whole slide imaging (WSI) finds increasingly higher value in everyday surgical pathology in addition to its well-established use for educational and research purposes. However, its diagnostic utility, especially in subspecialty settings such as neuropathology, is not fully validated. Neuropathology practice is unique with smaller overall tissue size and frequent need for high-power evaluation. In addition, tumor grade is an integral part of the initial diagnosis. The purpose of this study is to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…These pitfalls could limit the utility of WSI for accurate diagnosis and grading of tumors in surgical neuropathology. 2 However, in our study, those pitfalls reported by Pekmezci et al were not substantiated. After careful review of digitized slides we found that all discordant cases were attributed to misinterpretation as the image quality was good enough to appreciate the cytological details and to recognize mitotic figures (Figure 1A-D).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…These pitfalls could limit the utility of WSI for accurate diagnosis and grading of tumors in surgical neuropathology. 2 However, in our study, those pitfalls reported by Pekmezci et al were not substantiated. After careful review of digitized slides we found that all discordant cases were attributed to misinterpretation as the image quality was good enough to appreciate the cytological details and to recognize mitotic figures (Figure 1A-D).…”
Section: Discussioncontrasting
confidence: 90%
“…Fallon et al have shown a high correlation between frozen section slides and WSI with 52 ovarian frozen section diagnoses. 2 This accuracy rate maybe similar to neuropathology frozen sections. Several studies concluded that WSI as a diagnostic modality is not inferior to TLM.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…stated that the major reason for undergrading in brain tumor cases was the inability to recognize mitosis in WSI review. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%